A color-tunable single molecule white light emitter with high luminescence efficiency and ultra-long room temperature phosphorescence. Issue 2 (20th December 2020) - Ma, Xiao; Jia, Ling; Yang, Baozhu; Li, Jipeng; Huang, Wei; Wu, Dayu; Wong, Wai-Yeung
Abstract : A simple emitter could simultaneously achieve bright white light emission with high quantum yield, ultra-long phosphorescence and excitation-dependent color-tunable emission. Abstract : Developing organic single molecule white light emitters (SMWLE) with high luminescence efficiency, ultra-long phosphorescence (ULP) and excitation-dependent (ED) color-tunable emission is intriguing and highly desirable from theoretical research to practical application. Nevertheless, it is an extremely challenging topic. Here, it is found that three simple terpyridine-based derivatives (P1, P2 and P3 ) could exhibit unusual multiple emissions and interesting color-tunable emissions. In particular, P3 as the first example could simultaneously achieve bright white light emission with high quantum yield (49%), ultra-long phosphorescence ( τ = 0.57 s) and ED color-tunable emission under ambient conditions. Accordingly, it can achieve novel multicolor emission including yellowish green light, white light, blue light, bluish green light and red phosphorescence light in a very wide wavelength range. Both experimental and theoretical studies reveal that such novel emission characteristics are due to the fact that P3 integrates monomer, excimer, and intermolecular charge transfer (ICT) triple-mode emissions in the crystalline state. These results provide a rational strategy for the construction of SMWLE and ED color-tunable emission materials. Moreover, such simple multifunctional materials would show huge potential in displays, anti-counterfeiting, and so on.